Evaluasi Tata Kelola TI Pada Sekretariat DPRD Provinsi Sumatera Selatan Menggunakan Cobit 5 - damayanti, selvia (Jurnal EDik Informatika, 2018)
Information technology has long been used by the Secretariat of the DPRD of the Province of South Sumatra to support every process in the field of government, Secretariat of the DPRD of the Province of South Sumatra is in charge of organizing secretarial and financial administration, supporting the implementation of the tasks and functions of the DPRD and providing and coordinating experts needed by the DPRD of the Province of South Sumatra in implementing their rights and functions according to their needs. The purpose of this study is to identify, determine the condition and maturity level of IT governance and provide recommendations for improvements using the COBIT 5 framework. The results of the maturity level obtained from the average value of questionnaires are based on the domains EDM01, EDM 04, APO 01, APO 04, APO 07, BAI 02, BAI 08, DSS 01 dan MEA 01 which are 2.24 Managed Process.Keywords  : IT Governance, Cobit 5, Secretariat of the DPRD of the Province of                          South Sumatra